Self- and Cross-Aldol Condensation of Propanal Catalyzed by Anion-Exchange Resins in Aqueous Media - Pyo, Sang-Hyun; Hedström, Martin; Lundmark, Stefan; Rehnberg, Nicola ; 0000-0002-1326-5054; Hatti-Kaul, Rajni (Organic Process Research & Development, 2011)
Carbon-carbon bond formation using strong and weak anion-exchange resins as green catalysts for self- and cross-aldol condensation of propanal in aqueous media was investigated. The reaction pathway followed the route of aldol condensation to a beta-hydroxy aldehyde and dehydration to an alpha,beta-unsaturated aldehyde. The resulting products were further converted to hemiacetal, and/or acetal moieties, which were confirmed by FT-IR and NMR. In self-condensation using strong anion-exchange resin, 97% conversion of propanal was achieved with 95% selectivity to 2-methyl-2-pentenal within 1 h using 0.4 g/mL resin at 35 degrees C. The conversion and selectivity using weak anion exchanger was lower. During cross-aldol condensation of propanal with formaldehyde, 3-hydroxy-2-methyl-2-hydroxymethylpropanal was obtained as the main product through first and second cross-condensation followed by hydration reaction in acidic aqueous conditions. The strong anion-exchange resin provided maximal propanal conversion of 80.4% to the product with 72.4% selectivity after 7 h reaction at 35 degrees C and resin concentration of 1.2 g/mL. Using weak anion-exchange resin, the optimal conversion of propanal was 89.9% after 24 h at 0.8 g/mL resin and 35 degrees C, and the main product was 3-hydroxy-2-methylpropanal by first cross-aldol condensation along with relatively minor amounts of methacrolein and 3-hydroxy-2-methyl-2-hydroxymethylpropanal.